Effect of prehospital physician presence on Out-of-Hospital cardiac arrest (OHCA) patients undergoing extracorporeal cardiopulmonary resuscitation (ECPR): A secondary analysis of the SAVE-J II study - Futoshi Nagashima; Satoshi Inoue; Tomohiro Oda; Tomohiro Hamagami; Tomoya Matsuda; Makoto Kobayashi; Akihiko Inoue; Toru Hifumi; Tetsuya Sakamoto; Yasuhiro Kuroda (Resuscitation Plus)
Introduction: Extracorporeal cardiopulmonary resuscitation (ECPR) has been increasingly utilized for patients with out-of-hospital cardiac arrest (OHCA). However, the impact of prehospital physician presence on the outcomes of ECPR-treated OHCA patients remains uncertain. This study aimed to evaluate whether the presence of prehospital physicians improves 30-day survival and favorable neurological outcomes in this population. Methods: This retrospective study analyzed data from the SAVE-J II study, a nationwide multicenter cohort of OHCA patients treated with ECPR in Japan. Patients were divided into two groups: prehospital physician absence and prehospital physician presence. Propensity score matching (PSM) was performed using six covariates (age, sex, witness status, presence of bystander CPR, initial heart rhythm, and location of cardiac arrest) to adjust for baseline differences. Sensitivity analyses included PSM with additional covariates (prehospital time and Low flow time), inverse probability of treatment weighting (IPTW), and varying matching ratios. Primary and secondary outcomes were 30-day survival and favorable neurological outcome (Cerebral Performance Category [CPC] 1–2), respectively. Results: Of the 1,641 patients included, 448 were in the prehospital physician presence group and 1,193 in the prehospital physician absence group. Before PSM, 30-day survival rates were 28.2% (prehospital physician presence) vs. 25.7% (prehospital physician absence) (p = 0.350). After 1:1 PSM (6 covariates), the 30-day survival rate was significantly higher in the prehospital physician presence group (29.6%) compared to the prehospital physician absence group (22.7%) (p = 0.028), while favorable neurological outcomes showed no significant difference (prehospital physician presence: 14.5% vs. prehospital physician absence: 11.0%, p = 0.092). Sensitivity analyses confirmed the robustness of the findings, with 30-day survival consistently higher in the prehospital physician presence group across models, including 7-covariate PSM (31.8% vs. 23.0%, p = 0.009) and IPTW with 8 covariates (35.6% vs. 25.1%, p = 0.026). However, the 8-covariate IPTW model exhibited residual imbalance (SMD > 0.1 in four covariates). Favorable neurological outcomes did not show significant differences in any analysis. Conclusions: Prehospital physician presence was associated with improved 30-day survival in OHCA patients undergoing ECPR. However, favorable neurological outcomes did not show significant improvement. These findings highlight the need for strategies to optimize low-flow time and explore the potential role of prehospital ECPR initiation. Further prospective studies are required to validate these findings and improve outcomes in this critical population.